The concept of authority and its legitimacy: the problem of meaning and significance - Ihsan Abdulhady Naayb (The Scientific Journal of Cihan University– Sulaimaniya, 2017)
The concept is one of the most important elements in the construction of any theory, but one of the sociological concepts for the purpose of study and analysis is to identify and use it scientifically in order to know the nature of the phenomenon under discussion. The phenomenon of power is a matter of great interest by thinkers and researchers. It is also a phenomenon that is constantly developed and takes various forms of violence resulting from the will to control the other. As well as it was linked to all aspects of human relations.There are several problems facing the concept of power, including its meaning and significance, insofar as they are based on (right to govern) or (right of command and command) and, on the other hand, have a form of power for influence and control. Although philosophers and philosophers differed on the basis of authority, they agreed that it was moral and moral (power must obey). The nature of power also shows us its ambiguity, in that it is a substance or that it involves a relational concept that emphasizes (ability and influence). In addition, we find the practices of political power taking different forms and elements such as power, prestige, influence and control. In order to distinguish between power and power, this leads us to other problems such as the concept of power and authority, If the concept of legality does not ostensibly raise any real problem, in that everything that is in line with the provisions of the laws in force is lawful, the concept of legality raises a wide controversy, as it transforms power into a legitimate authority and justifies submission and obedience.